2003
DOI: 10.1086/368128
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusAccessory Gene Regulator(agr)Group II: Is There a Relationship to the Development of Intermediate‐Level Glycopeptide Resistance?

Abstract: We previously determined that all 6 Staphylococcus aureus strains with confirmed intermediate-level resistance to glycopeptides (glycopeptide intermediate S. aureus [GISA]) from the United States that we tested belonged to accessory gene regulator (agr) group II. In the present study, we found that 56% of surveyed bloodstream methicillin-resistant S. aureus isolates (n = 148) at our hospital were agr group II, whereas only 24% of methicillin-susceptible S. aureus isolates (n = 33) were agr group II (P = .001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
148
4
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 40 publications
6
148
4
2
Order By: Relevance
“…It has been suggested that the acquisition of antibiotic resistance in S. aureus involves changes in virulence factor secretion due to the fitness cost associated with the expression of resistance (Sakoulas et al 2003, Gill et al 2005 and it is reflected in decreased toxin expression (Collins et al 2010, Otto 2010. Therefore, it is not surprising that the results of the present study confirmed this by showing that virulence factor gene carriage was more diverse and abundant in MSSA than in MRSA strains.…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that the acquisition of antibiotic resistance in S. aureus involves changes in virulence factor secretion due to the fitness cost associated with the expression of resistance (Sakoulas et al 2003, Gill et al 2005 and it is reflected in decreased toxin expression (Collins et al 2010, Otto 2010. Therefore, it is not surprising that the results of the present study confirmed this by showing that virulence factor gene carriage was more diverse and abundant in MSSA than in MRSA strains.…”
Section: Discussionsupporting
confidence: 81%
“…A number of studies have linked alterations in agr activation or function with vancomycin tolerance, an increased tendency to develop vancomycin resistance, and the presence of the hVISA or VISA phenotype (121,269,295,296,357). In a number of these studies, determinations of agr activity were performed by the analysis of delta-hemolysin production on sheep blood agar; however, this is only a semiquantitative measure (296).…”
Section: Accessory Gene Regulator (Agr)mentioning
confidence: 99%
“…Initially, it appeared that agr group II isolates were overrepresented in VISA strains from around the world (369); however, a subsequent study from Europe demonstrated that many of their VISA and hVISA isolates were of agr group I (295,296). In addition, it was demonstrated that S. aureus from agr groups I to IV all develop intermediate vancomycin resistance upon in vitro exposure to the drug (358).…”
Section: Accessory Gene Regulator (Agr)mentioning
confidence: 99%
See 2 more Smart Citations